Baltic Sea in Estonian and Finnish media : discussed topics and stakeholders - Jaagus, Triin (2016)
In this paper the stakeholders and most discussed topics of Baltic Sea in the media are examined. Baltic Sea is a fragile ecosystem that provides variety of services to the locals. Not only the locals hold the stake, but also industries and governments. This paper aims to present the complexity of stakeholder network and contradicting interests. Altogether 104 newspaper articles from Estonian and Finnish media on Baltic Sea were used as the data source and the concerning topics, themes and stakeholders were surveyed. The qualitative data was inserted to the textual analysis software QDA Miner 4 Lite. Three main topics were named according to the concept of three pillars of sustainability- economy, environment and society. Themes in these topics were also listed to further investigate the content of articles. Environment proved to be most presented topic whereas widely discussed themes were pollution and co-operation. It was also noted that country, newspaper and time of publishing had impact on the content. The stakeholder analysis was conducted by creating MAW-model and influence diagram for the listed stakeholders. In this research the main results on stakeholders were the list of stakeholders, their relevancy and connections between them. The thesis contributes to the understanding of the complexity of interests hold in the Baltic Sea and the need for integrated and international management approach. Media analysis approach indicates how Baltic Sea issues are presented to the public and which topics and stakeholders are most relevant based on media’s presentation.